2007
DOI: 10.1007/s10641-007-9310-x
|View full text |Cite
|
Sign up to set email alerts
|

Circannual vitellogenin levels in Chinese loach (Misgurnus anguillicaudatus)

Abstract: To improve the use of the Chinese loach, Misgurnus anguillicaudatus, as a sentinel species for environmental investigations, normal ranges of plasma vitellogenin (Vtg) was studied. Male and female loaches were collected every 2 months from November 2004 to September 2005, and a specific and sensitive competitive enzyme-linked immunosorbent assay (ELISA) was used to determine plasma Vtg levels. Our data indicated that the average maximum Vtg level of female loaches (757±356 µg mL −1 ) appeared in March, approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The loach, for a long time, had been considered as traditional Chinese medicine in folk remedies for treatment of hepatitis, osteomyelitis, carbuncles, inflammation and cancer, as well as for restoration to health in debilities caused by various pathogens and aging (Qin et al 2002), some active substances obtained from loach were proved to be of high medical value (Kimura et al 1994;Dong et al 2002;Huang 2005, 2006). Moreover, the loach can be used as an ideal model animal in genetics and toxicology (Khan and Arai 2000;Shao et al 2005;Lv et al 2006Lv et al , 2007Lv et al , 2008; Morishima et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The loach, for a long time, had been considered as traditional Chinese medicine in folk remedies for treatment of hepatitis, osteomyelitis, carbuncles, inflammation and cancer, as well as for restoration to health in debilities caused by various pathogens and aging (Qin et al 2002), some active substances obtained from loach were proved to be of high medical value (Kimura et al 1994;Dong et al 2002;Huang 2005, 2006). Moreover, the loach can be used as an ideal model animal in genetics and toxicology (Khan and Arai 2000;Shao et al 2005;Lv et al 2006Lv et al , 2007Lv et al , 2008; Morishima et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma vitellogenin concentration has been shown to peak during vitellogenesis (i.e. before spawning) in several other species, including Chinese loach Misgurnus anguillicaudatus (Lv et al, 2009), Senegalese sole (Guzmán et al, 2008), amberjack (Mandich et al, 2004) and gilthead seabream (Mosconi et al, 1998). On the other hand, vitellogenin in the more closely related Atlantic halibut peaked during spawning (Methven et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fish are easy to work with and their endocrine systems are similar to those of higher vertebrates. Moreover, studies have demonstrated that fish suffer from the interference of EDCs in their habitats and entire life cycle (Lv et al 2009). Therefore, the majority of the investigations on EDCs have focused on the aquatic environment using fish as experimental models (Pait and Nelson 2003).…”
Section: Introductionmentioning
confidence: 99%